Tissue-specific inflammation and insulin sensitivity in subjects with obesity - Oussaada, S.M.; Kilicarslan, M.; de Weijer, B.A.; Gilijamse, P.W.; Şekercan, A.; Virtue, S.; Janssen, I.M.C.; van de Laar, A.; Demirkiran, A.; van Wagensveld, B.A.; Houdijk, A.P.J.; Jongejan, A.; et al. (Diabetes research and clinical practice, 2024)
Obesity is associated with low-grade inflammation and insulin resistance (IR). The contribution of adipose tissue (AT) and hepatic inflammation to IR remains unclear. We conducted a study across three cohorts to investigate this relationship. The first cohort consists of six women with normal weight and twenty with obesity. In women with obesity, we found an upregulation of inflammatory markers in subcutaneous and visceral adipose tissue, isolated AT macrophages, and the liver, but no linear correlation with tissue-specific insulin sensitivity. In the second cohort, we studied 24 women with obesity in the upper vs lower insulin sensitivity quartile. We demonstrated that several omental and mesenteric AT inflammatory genes and T cell-related pathways are upregulated in IR, independent of BMI. The third cohort consists of 23 women and 18 men with obesity, studied before and one year after bariatric surgery. Weight loss following surgery was associated with downregulation of multiple immune pathways in subcutaneous AT and skeletal muscle, alongside notable metabolic improvements. Our results show that obesity is characterised by systemic and tissue-specific inflammation. Subjects with obesity and IR show a more pronounced inflammation phenotype, independent of BMI. Bariatric surgery-induced weight loss is associated with reduced inflammation and improved metabolic health.